The influence of existential group therapy of the purpose in life, values and interpersonal relationships of third year psychology students - Van Wijk, Gillian Murray (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1995.